2006
DOI: 10.1073/pnas.0511232103
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of an equilibrative nucleoside transporter by cannabidiol: A mechanism of cannabinoid immunosuppression

Abstract: The plant-derived cannabinoids ⌬ 9 -tetrahydrocannabinol (THC) and cannabidiol (CBD) both have immunosuppressive effects; although some effects of THC are mediated by the CB2 receptor, CB2 binds CBD weakly. In examining the effects of THC and CBD on microglial proliferation, we found that these compounds potently inhibit [ 3 H]thymidine incorporation into a murine microglial cell line with no effect on cell cycle. Because adenosine agonists have antiinflammatory effects, and because uptake of adenosine is a pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
326
1
12

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 417 publications
(344 citation statements)
references
References 36 publications
5
326
1
12
Order By: Relevance
“…In previous studies, CBD has been shown to exert anti-inflammatory effects, but a distinct mechanism of action for this effect remains unresolved [106], despite hypotheses that CBD exerts anti-inflammatory effects by facilitating adenosine transmission [10,106]. To test this hypothesis, the effect of CBD on the uptake of [ 3 H]-adenosine was investigated (see Table 4).…”
Section: Neurotransmitter Transportersmentioning
confidence: 99%
See 2 more Smart Citations
“…In previous studies, CBD has been shown to exert anti-inflammatory effects, but a distinct mechanism of action for this effect remains unresolved [106], despite hypotheses that CBD exerts anti-inflammatory effects by facilitating adenosine transmission [10,106]. To test this hypothesis, the effect of CBD on the uptake of [ 3 H]-adenosine was investigated (see Table 4).…”
Section: Neurotransmitter Transportersmentioning
confidence: 99%
“…Further studies, which examined the affinity of CBD for the equilibrative nucleoside transporter 1 (ENT1) showed that CBD displaced radiolabelled 6-S-[(4-Nitrophenyl)methyl]-6-thioinosine ([ 3 H]-NMBPR) with a K i value of 237 nM, consistent with the result obtained from RAW264.7 macrophages. These findings indicate that CBD can inhibit adenosine uptake by binding ENT1 [106]. Thus, while it is clear that CBD can modulate adenosine signaling at both the receptor (see BReceptors^) and transporter levels, the contribution of these effects to the in vivo pharmacology of CBD still requires definitive study.…”
Section: Neurotransmitter Transportersmentioning
confidence: 99%
See 1 more Smart Citation
“…CBD inhibits uptake of adenosine by blocking the equilibrative nucleoside transporter [118,119]. Increased levels of adenosine activate A2 receptors, which regulate striatal CB 1 Rs [120].…”
Section: Cbdmentioning
confidence: 99%
“…Human nucleoside transporters are classified into three known isoforms of concentrative nucleoside transporters (CNT) that are coupled to a Na + gradient (Gray et al, 2004;Smith et al, 2007) and into four known isoforms of equilibrative nucleoside transporters (ENT), which rapidly equilibrate pools of extra-and intracellular adenosine (Baldwin et al, 2004). Under physiological conditions ENTs appear to play the predominant role in adjusting extra-and intracellular pools of adenosine in the brain, since the extracellular concentration of adenosine can be enhanced by inhibition of ENTs with dipyridamole, dilazep, nitrobenzylthioinosine, or cannabidiol (Carrier et al, 2006;Kong et al, 2004).…”
Section: Nucleoside Transportersmentioning
confidence: 99%